Identifying cultural difference in R&D project for performance improvement: A field study - Zeng, S. X.; Xie, X. M.; Tam, C. M.; Sun, P. M. (Journal of Business Economics and Management, 2009)
In recent years, some large multinational companies have begun moving their R&D centers to China. As a result, cross‐cultural management for R&D projects becomes challenging due to the cultural diversity. Based on the technique of relative importance index (RII), this study examines the gaps between the Chinese and Western cultures in R&D projects for multinational firms. The findings show there is a significant difference between Chinese and Western cultures. The top five factors transformed into self‐reflection statements include: 1) You could accept your manager criticizing your mistake in public; 2) You avoid any conflict with your manager; 3) Objective of the project is the target for the whole project group; 4) You do not mind the methods for your performance evaluation; and 5) You pay greater attention to improve “relationship” among colleagues. Overall, these findings reveal managerial implications for R&D managers that the need to recognize and manage cultural difference is an important component in cross‐cultural project management.First Publish Online: 14 Oct 2010